An Exploration of the Impact of Industry 4.0 Approach on Corporate Communication in the German Manufacturing Industry - Georg Hauer; Patrick Harte; Jasmin Kacemi (International Journal of Supply Chain Management, 2018)
The purpose of this study is to explore the impact of the Industry 4.0 approach on Corporate Communication in the German manufacturing industry. Industry 4.0 is currently one of the most discussed topics within the German industry with its aim to strengthen the competitiveness of German manufacturers. Industry 4.0 comprises the entire life-cycle of a product through an intelligent networked production. Smart factories symbolize the main objective of Industry 4.0 by implementing Cyber-Physical Systems, the Internet of Things and Internet of Services. The impact of Industry 4.0 on Corporate Communication has not yet been investigated. Therefore, a significant gap of research exists, which will be closed by this study on the impacts of Industry 4.0 on internal as well as external communication. The study was conducted through primary data collection, using a mono-method qualitative research technique in form of semi-structured expert interviews. The sampling comprises six interviewees from varying industry sectors in Germany. The interview partners were chosen due to their expertise on thematic aspects of Corporate Communication and/or Industry 4.0 within organisations which deal with Industry 4.0 implementations. The sampling represents different perspectives on Industry 4.0 as it illustrates different Industry 4.0 operators and Industry 4.0 service providers. Data is examined by a thematic analysis approach involving a vertical and horizontal analysis of the cases. Deriving from the data analysis and findings, an overview of the impact and potential opportunities for manufacturers is formulated. Lastly, to conclude the topic a prospective outlook will be given.